Juan Luis de la Cerda y la crítica textual: una apostilla al catálogo de manuscritos latinos del Prof. Lisardo Rubio - Andréz Tabárez (Exemplaria Classica, 2009)
The aim of this paper is to trace the true authorship of a manuscript collation of Virgil’s Eclogues wrongly attributed to Juan Luis de la Cerda.